Effect of market orientation, learning orientation and entrepreneurial orientation on sme's performance in the Pakistan context - Arshad, Muhammad Hassan (2018)
This study aims to investigate the effect of Market Orientation (MO), Entrepreneurial Orientation (EO), Learning Orientation (LO) and Performance (P). The study was greatly motivated by the inconsistent findings and the gaps indicated in the contemporary literature regarding those relationships. First there were contradictory findings between EO and Performance, MO and Performance and LO and Performance relationships. Second, the three strategies; MO, EO and LO were not investigated together within the context of Small and Medium Enterprises (SMEs). Data were collected from SMEs operating in the Punjab Province, Pakistan. By using questionnaire survey, and a random sampling was used for sample selection. 380 questionnaires were distributed to SME owner/managers but only 330 of them were returned, giving a response rate of 83 percent. Only 318 useable questionnaires were used for further analysis. The findings revealed that EO, MO and LO were significantly related to performance. The findings of this study provided significant insights for both managers and researchers to further understand the effects of implemented strategies on performance. Finally, limitations of study and necessary recommendations for future research were discussed.